Self-Care: An Act of Political Warfare or a Neoliberal Trap?. Issue 1 (September 2017) - Michaeli, Inna
Abstract There is a momentum for self-care and well-being in feminist movements. Beyond neoliberal trends, we can find deeply politicized and inter-generational practices of care, and feminist ways of conceiving self-care and collective care, building sustainable and transformative organizations and movements, and comprehending what being well means in situations of injustice. In different corners on the world, feminists are developing provocative and creative models of care for survivors of violence, human rights defenders, activists, and organizations.